2006
DOI: 10.1016/j.ijsolstr.2005.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple directional damages in a thin cylindrical shell

Abstract: In this paper, a structural damage identification method (SDIM) is developed to identify the line crack-like directional damages generated within a cylindrical shell. First, the equations of motion for a damaged cylindrical shell are derived. Based on a theory of continuum damage mechanics, a small material volume containing a directional damage is represented by the effective orthotropic elastic stiffness, which is dependent of the size and the orientation of the damage with respect to the global coordinates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The WT has a certain ability to denoise ultrasonic signals, but needs to go through a complex process to obtain the wavelet threshold and threshold function. Moreover, the WT may distort the original signals, leading to discrete and oscillating signals [2][3][4]. The AF relies on the selection of the reference signal, which is not always correlated with the noise signals [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The WT has a certain ability to denoise ultrasonic signals, but needs to go through a complex process to obtain the wavelet threshold and threshold function. Moreover, the WT may distort the original signals, leading to discrete and oscillating signals [2][3][4]. The AF relies on the selection of the reference signal, which is not always correlated with the noise signals [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…With the extension of the service time of the industrial pipes, the damage caused by material defects, corrosion, or external force, makes the pipeline security situation gradually deteriorated. A lot of nondestructive testing technologies are available to inspect defected pipes [1][2][3]. However, they are time-consuming works because every industrial pipe needs to be tested by placing huge number of sensors for most conventional nondestructive tests.…”
Section: Introductionmentioning
confidence: 99%
“…Ip and Tse [24] proposed an approach based on frequency sensitivities and mode shapes; Sarker et al [25] also demonstrated that the curvature of mode shapes was sensitive to local damage. Lee et al [26][27] illustrated that multiple directional damages can be identified by using Frequency Response Functions (FRFs). Other researchers developed several promising approaches based on advanced dynamic properties.…”
Section: Introductionmentioning
confidence: 99%